Audiovisual Content of War Photojournalism and Social Audience - Sandulescu Budea, Alexandra; Rivera Martín, Beatriz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Analysis of the new freelance war photojournalist profile and their relationship with the social audience. The aim is to reveal what relationship they maintain with the social audience of their social networks in order to update the concept of the freelance war correspondent profile. To this end, a mixed methodology has been used, combining quantitative analysis such as content analysis and qualitative analysis such as critical discourse analysis. The main conclusion is the possibility of having an impact on citizens without depending on a media outlet or interests positioned on the conflict being reported.